Predictors of Linkage to and Retention in HIV Care Following Release from Connecticut Jails and Prisons. (4th October 2017) - Loeliger, Kelsey B; Altice, Frederick L; Desai, Mayur M; Ciarleglio, Maria M; Gallagher, Colleen; Meyer, Jaimie P
Abstract: Background: One in six people living with HIV (PLH) in the USA transition through prison or jail annually. During incarceration, people may engage in HIV care, but transition to the community remains challenging. Linkage to care (LTC) post-release and retention in care (RIC) are necessary to optimizing HIV outcomes, but have been incompletely assessed in prior observational studies. Methods: We created a retrospective cohort of all PLH released from a Connecticut jail or prison (2007–2014) by linking Department of Correction demographic, pharmacy, and custody databases with Department of Public Health HIV surveillance monitoring and case management data. We assessed time to LTC, defined as time from release to first community HIV-1 RNA test, and viral suppression status at time of linkage. We used generalized estimating equations to identify correlates of LTC within 14 or 30 days after release. We also described RIC over three years following an initial release, comparing recidivists to non-recidivists. Results: Among 3, 302 incarceration periods from 1, 350 unique PLH, 21% and 34% had LTC within 14 and 30 days, respectively, of which >25% had detectable viremia at time of linkage. Independent correlates of LTC at 14 days included incarceration periods >30 days (adjusted odds ratio [AOR] = 1.6; P  < 0.001), higher medical comorbidity (AOR = 1.8; P  < 0.001), antiretrovirals prescribed before release (AOR = 1.5; P  = 0.001), transitional case management (AOR = 1.5; P  < 0.001), re-incarceration (AOR = 0.7; P  = 0.002) and conditional release (AOR = 0.6; P  < 0.001). The 30-day model additionally included psychiatric comorbidity (AOR = 1.3; P  = 0.016) and release on bond (AOR = 0.7; P  = 0.033). Among 1, 094 PLH eligible for 3-year follow-up, RIC after release declined over 1 year (67%), 2 years (51%) and 3 years (42%). Recidivists were more likely than nonrecidivists to have RIC but, among those retained, were less likely to be virally suppressed (Figure 1). Conclusion: For incarcerated PLH, both LTC and RIC as well as viral suppression are suboptimal after release. PLH who receive case management are more likely to have timely LTC. Targeted interventions and integrated programming aligning health and criminal justice goals may improve post-release HIV treatment outcomes. Disclosures: All authors: No reported disclosures.